2013
DOI: 10.1017/thg.2012.152
|View full text |Cite
|
Sign up to set email alerts
|

Current Practice and Attitudes of Australian Obstetricians Toward Population-Based Carrier Screening for Inherited Conditions

Abstract: An anonymous survey of Australian Fellows of the Royal Australian and New Zealand College of Obstetricians and Gynaecologists was conducted with the aim of understanding current practice and attitudes toward population-based carrier screening for inherited conditions in the setting of routine pregnancy care. Of 1,121 Fellows invited to complete the online questionnaire by e-mail, 237 (21%) responded, and of these 156 were practicing obstetricians and completed the whole survey. Of the respondents, 83% expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 27 publications
5
30
0
Order By: Relevance
“…The attitudes of obstetricians to CF carrier screening were addressed by an online questionnaire sent to 1121 Australian obstetricians in 2011 . Of the 237 respondents, 83% supported carrier screening for CF and 97% supported carrier screening for β‐thalassaemia.…”
Section: Resultsmentioning
confidence: 99%
“…The attitudes of obstetricians to CF carrier screening were addressed by an online questionnaire sent to 1121 Australian obstetricians in 2011 . Of the 237 respondents, 83% supported carrier screening for CF and 97% supported carrier screening for β‐thalassaemia.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Stark et al (2013) showed that barriers identified by Australian obstetricians in regard to routinely offering genetic (not just CF) carrier screening were: time constraints, costs and availability of supporting services. A lack of knowledge and experience in regard to CF and genetic screening has also been indicated as a barrier, with health professionals not feeling confident in their ability to provide screening to their patients, which may contribute to women's reasons for declining screening.…”
Section: Discussionmentioning
confidence: 99%
“…These international studies explored various factors such as preferences, familiarity and perceived benefits or risk. Previous research in Australia has included obstetricians29 or qualitatively explored themes surrounding carrier screening 30…”
Section: Introductionmentioning
confidence: 99%